Biomechanic and histologic analysis of fibroblastic effects of tendon-to-bone healing by transforming growth factor β1 (TGF-β1) in rotator cuff tears - Zhang,Chong (2017)
Abstract Purpose: To evaluate the effect of transforming growth factor β1 (TGF-β1) on tendon-to-bone reconstruction of rotator cuff tears. Methods: Seventy-two rat supraspinatus tendons were transected and reconstructed in situ. At 8 and 16 weeks, specimens of three groups; that is control, L-dose (low dose), and H-dose (high dose) were harvested and underwent a biomechanical test to evaluate the maximum load and stiffness values. Histology sections of the tendon-to-bone interface were identified by hematoxylin-eosin or Masson trichrome stain. Collagen type III was observed by picric acid sirius red staining under polarized light. The level of insulin-like growth factor 1 (IGF-1) and vascular endothelial growth factor (VEGF) was measured by the enzyme-linked immunosorbent assay (ELISA) method. Results: Collagen type III of the H-dose group had a significant difference in histology structure compared with the L-dose group (P<0.05). The maximum load and stiffness decreased significantly in the control group compared with the values of the L-dose and H-dose groups. The stiffness among the three groups differed significantly at the same postoperative time (P<0.05). Interestingly, progressive reestablishment of collagen type III affected tendon-to-bone healing significantly in the later stages. Conclusion: The H-dose was associated with an increased collagen type III morphology stimulated by TGF-β1.